THE INITIATIVE TO RAISE AWARENESS ON STUNTING AMONG HEALTH CADRES IN WONOKROMO VILLAGE: UPAYA PENINGKATAN KESADARAN STUNTING PADA KADER KESEHATAN DI DESA WONOKROMO - Hanik, Umi; Setianto, Budhi; Aan Adriansyah, Agus; Nila Karmila, Hartatiek; Susantri, Mery; Sa'adah, Nikmatus (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Stunting is associated with various short-term effects such as developmental delays, decreased immune function, impaired cognitive function, and compromised metabolic systems. Furthermore, long-term consequences may include obesity, reduced glucose tolerance, coronary heart disease, hypertension, and osteoporosis. The limited understanding among healthcare cadres regarding comprehensive treatment necessitates interventions to aid in the assistance and recovery of infants identified as stunted. Objective: This activity aims to enhance the knowledge level concerning stunting among healthcare cadres. Method: The initiative will take the form of lectures, discussions, and case studies targeting 68 women from RW 07 cadres in Wonokromo Village. The stunting counseling event for RW 07 Health Cadre, Wonokromo Village, held on July 9 2023, was met with enthusiasm. Results: The presentation emphasized the significance of preventing stunting and highlighted the "1000 First Day of Life" initiative. The outreach activity effectively enhanced knowledge regarding stunting incidence, with 68 participants actively engaged, primarily comprising women aged 36 to 45 years, predominantly housewives. Conclusion: Analysis of pre-test and post-test results revealed a notable increase of 19.2%. Furthermore, the paired t-test demonstrated a significant difference between the pre-test and post-test (α = 5%).